Easy PCs : See it Done, Do it Yourself - Gertler, Nat. ([Indianapolis, IN] : Que, 1998)
A visual guide to microcomputers, windows, and the Internet.
Includes index.
Keywords: Microsoft Windows (Computer file); Microcomputers